2017
DOI: 10.3329/bmjk.v49i1-2.31820
|View full text |Cite
|
Sign up to set email alerts
|

Safety & efficacy of manual vacuum aspiration compared to dilatation & curettage in the management of early pregnancy failure

Abstract: Background: Early pregnancy failure is a major health problem across the globe. This is particularly important for the woman of Bangladesh.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…As per World Health Organization (WHO) recommendations, shifting from sharp dilation and curettage (D&C) to the use of aspiration techniques, notably manual vacuum aspiration (MVA) and medical treatment with misoprostol for PAC, improves health outcomes and expands the availability of services through task shifting 8 . In addition to improving safety, the shift away from D&C reduces the length of in-patient hospital stays, reduces the time required for recovery, and is more cost-effective overall 9 , 10…”
Section: Introductionmentioning
confidence: 99%
“…As per World Health Organization (WHO) recommendations, shifting from sharp dilation and curettage (D&C) to the use of aspiration techniques, notably manual vacuum aspiration (MVA) and medical treatment with misoprostol for PAC, improves health outcomes and expands the availability of services through task shifting 8 . In addition to improving safety, the shift away from D&C reduces the length of in-patient hospital stays, reduces the time required for recovery, and is more cost-effective overall 9 , 10…”
Section: Introductionmentioning
confidence: 99%
“…D and C is considerably more painful for women and less safe than vacuum aspiration. 24,25 Islam et al in their study on the management of early pregnancy failure in Bangladesh, found that MVA is safe, effective, cheaper, and complication is also less than D and C. 26 Cochrane systematic review by Tuncalp et al also found MVA is faster, less painful, and associated with less blood loss and fewer complications than D and C in the management of incomplete miscarriage. 27 Clinical practice handbook for safe abortion by WHO (2014) reemphasizes that within the framework of national laws, providers should promote and protect: women's and adolescents' health and their human rights; informed and voluntary decision-making; and autonomy in decisionmaking.…”
Section: Discussionmentioning
confidence: 99%
“…The mean gestational age being 8.55 ± 1.6 weeks and 8.51 ± 1.7 week for MVA and D&C groups respectively. Islam et al (2016) in Bangladesh in [16] described findings as the maximum number of gestational age ranged from 9 to 11 weeks, median gestational age being 9.3 weeks and 9.5 weeks for each procedure. Our study is also compatible with the findings of Fatima et al (2020) in Pakistan, in [20] reported the mean gestational age was 8.46+ 1.88 and 8.32+ 1.56 week for women treated by D & C and MVA respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete uterine evacuation was seen in 4.2% (3/72) patients in MVA group whereas it was seen in 1.4% (1/71) patients in D&E group. Islam et al (2016) in [16] from Bangladesh did not show much difference as far as their effectiveness was concern (97% in MVA and 99% in curettage group). Several studies done elsewhere show the same result for MVA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation